The murky future of global water quality: New global study projects rapid deterioration in water quality - International Food Policy Research Institute; VEOLIA (International Food Policy Research Institute, 2015)
Even using the most optimistic projections, the world is on a path toward rapidly deteriorating water quality levels in many countries, according to a new study conducted by the International Food Policy Research Institute and Veolia. The study uses robust mathematical modeling to contrast specific biophysical water quality modeling on a global scale with three global economic projections, two sets of climate change projections and projected future agricultural production activities. Water quality deterioration is projected to rapidly increase over the next several decades which, in turn, will increase risks to human health, economic development and ecosystems. The findings in this study serve as a call to action to contain water pollution to ensure that future generations can enjoy the many benefits associated with clean water